Relevance of the Iron Distribution in Natural Smectite Clays for the Thermal Stability of PMMA-Clay Nanocomposites - Ferreira, Camila R. [UNESP]; Santilli, Celso V. [UNESP]; Briois, Valérie; Pulcinelli, Sandra H. [UNESP] (American Chemical Society (ACS), 2024)
Polymer-clay nanocomposites have greater thermal stability compared to the pristine polymer matrix. This can be attributed to the physical barrier provided by the inclusion of 2D clay nanoparticles (especially of the smectite group), together with radical trapping related to the distribution of specific 3d atoms in the inorganic phase. To elucidate the relevance of the Fe3+ distribution in this synergic effect, the iron atoms present in octahedral sheets of natural nontronite clay (Non, 5.6 wt % Fe) or in maghemite (M) nanoparticles (γ-Fe2O3) were incorporated in a poly(methyl methacrylate) (PMMA) matrix. Na-laponite (Lap) clay was used to evaluate the contribution of the diffusion barrier effect to the increased thermal stability of a PMMA-Lap nanocomposite, as evidenced by the upshift of the thermogravimetric (TGA) curve compared to that for PMMA. The contribution of radical trapping to the thermal stability of the PMMA-Non nanocomposite was evidenced by a significant shift of the Fe K-edge rising edge position by −4.5 eV after iron reduction by heating in N2, while similar treatment of pristine nontronite did not lead to a significant rising edge shift in the X-ray absorption spectra (XAS). This downshift demonstrated the reduction of Fe3+ to Fe0, induced by the sequestration of radicals formed by PMMA depolymerization. Raman spectroscopy analysis evidenced the formation of graphitic char deposits above 400 °C, further improving the thermal stability of PMMA-Non by providing an additional physical barrier to mass transport. A fourth contribution of well-dispersed iron was the abstraction of carbon from the char by the iron carburization reaction, which hindered CO2 formation by oxidative coking. In contrast, no relevant contribution of graphitic layer deposition was observed for the PMMA-M-Lap nanocomposite, where its improved thermal stability was only due to the combined contributions of the gas diffusion barrier effect and radical trapping by iron atoms. The maghemite effectively captured the radicals confined by the clay sheets, resulting in significant stabilization of the nanocomposite, with a shift of the mass loss of the PMMA-M-Lap nanocomposite compared to PMMA-Lap.